A critical review of cell culture strategies for modelling intracortical brain implant material reactions. (June 2016) - Gilmour, A.D.; Woolley, A.J.; Poole-Warren, L.A.; Thomson, C.E.; Green, R.A.
Abstract: The capacity to predict in vivo responses to medical devices in humans currently relies greatly on implantation in animal models. Researchers have been striving to develop in vitro techniques that can overcome the limitations associated with in vivo approaches. This review focuses on a critical analysis of the major in vitro strategies being utilized in laboratories around the world to improve understanding of the biological performance of intracortical, brain-implanted microdevices. Of particular interest to the current review are in vitro models for studying cell responses to penetrating intracortical devices and their materials, such as electrode arrays used for brain computer interface (BCI) and deep brain stimulation electrode probes implanted through the cortex. A background on the neural interface challenge is presented, followed by discussion of relevant in vitro culture strategies and their advantages and disadvantages. Future development of 2D culture models that exhibit developmental changes capable of mimicking normal, postnatal development will form the basis for more complex accurate predictive models in the future. Although not within the scope of this review, innovations in 3D scaffold technologies and microfluidic constructs will further improve the utility of in vitro approaches.